Lipocalin‐2 Protects Against Diet‐Induced Nonalcoholic Fatty Liver Disease by Targeting Hepatocytes - Xu, Yanyong (Hepatol Commun, 2019)
Hepatocytes are the major source of hepatic lipocalin‐2 (LCN2), which is up‐regulated in response to inflammation, injury, or metabolic stress. So far, the role of hepatocyte‐derived LCN2 in the development of nonalcoholic fatty liver disease (NAFLD) remains unknown. Herein we show that overexpression of human LCN2 in hepatocytes protects against high fat/high cholesterol/high fructose (HFCF) diet–induced liver steatosis and nonalcoholic steatohepatitis by promoting lipolysis and fatty acid oxidation (FAO) and inhibiting de novo lipogenesis (DNL), lipid peroxidation, and apoptosis. LCN2 fails to reduce triglyceride accumulation in hepatocytes lacking sterol regulatory element‐binding protein 1. In contrast, Lcn2(−/−) mice have defective lipolysis, increased lipid peroxidation and apoptosis, and exacerbated NAFLD after being fed an HFCF diet. In primary hepatocytes, Lcn2 deficiency stimulates de novo lipogenesis but inhibits FAO. Conclusion: The current study indicates that hepatocyte LCN2 protects against diet‐induced NAFLD by regulating lipolysis, FAO, DNL, lipid peroxidation, and apoptosis. Targeting hepatocyte LCN2 may be useful for treatment of NAFLD.